A novel multiresistance gene cluster located on a plasmid-borne transposon in Listeria monocytogenes. (23rd January 2020) - Yan, He; Yu, Runhao; Li, Dexi; Shi, Lei; Schwarz, Stefan; Yao, Hong; Li, Xin-Sheng; Du, Xiang-Dang
Abstract: Objectives: To identify the genetic context and the transferability of the multiresistance gene lsa (E) in Listeria monocytogenes . Methods: MICs were determined by broth microdilution. Transferability of lsa (E) was investigated by conjugation, electrotransformation and natural transformation. The lsa (E)-carrying plasmid was sequenced using the Illumina MiSeq and PacBio RSII platforms. The presence of translocatable units (TUs) was examined by PCR. Results: The 85 555 bp non-conjugative multiresistance plasmid pNH1 from L. monocytogenes harboured nine antimicrobial resistance genes including a multiresistance gene cluster, consisting of the genes aphA3, erm (B), aadE, spw, lsa (E) and lnu (B), and in addition the genes dfrG, tet (S) and catA8 were also located on plasmid pNH1 The multiresistance gene cluster, and each of the genes tet (S), catA8 and cadA were flanked by IS 1216 elements. PCR identified four types of TUs, consisting of either the multiresistance gene cluster and one copy of IS 1216, the catA8 gene and one copy of IS 1216, or both, but also the tet (S) gene and one copy of IS 1216, respectively. Natural transformation into Streptococcus mutans UA159 yielded transformants that harboured a novel 13 208 bp transposon, designated Tn 6659. This transposon consisted of the multiresistance gene cluster bounded by IS 1216 copies. All transformants displayed elevated MICs of the respective antimicrobial agents. At the integration site in the transformants, 8 bp direct target duplications (5′-ATTCAAAC-3′) were found immediately up- and downstream of Tn 6659 . Conclusions: To the best of our knowledge, this is the first report of this novel multiresistance gene cluster and the gene catA8, flanked by IS 1216 elements located on a plasmid of L. monocytogenes . Moreover, a novel functionally active multiresistance transposon was identified.